PLANT-BASED NATURAL DYES IN MONTASIK DISTRICT - Eriawati; Nurdin Amin; Ita Kausari (Barkah Publishing, 2026)
Additive substances are materials deliberately added to food to influence its properties and characteristics. These additives include, among others, food colorings and flavor enhancers. Food coloring refers to substances used to impart or improve the color of food, whereby natural colorings are derived from plants that have the potential to produce various hues. This study aims to identify plant species used as natural dye materials by the community in Montasik. The research employs a qualitative descriptive approach using purposive sampling. Data were collected through interviews, observation, and documentation. The findings reveal 13 plant species used as natural dyes, belonging to 10 families. The results indicate that pandan (Pandanus amaryllifolius) was used by 70 respondents, suji (Dracaena angustifolia) by 67 respondents, Kunyit (Curcuma longa L.) by 65 respondents, Kembang telangflower (Clitoria ternatea) likewise by 65 respondents, and purple sweet potato (Ipomoea batatas L.) by 60 respondents.